2018
DOI: 10.1159/000492289
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Potassium Concentration Alleviates Cerebral Ischemia-Reperfusion Injury via Mitochondrial Preservation

Abstract: Background/Aims: The anti-apoptotic effect of an increase in the extracellular concentration of potassium ([K+]) has been confirmed in vitro. However, it is not yet known whether elevated serum [K+] exerts a cerebroprotective effect in vivo. In this study, we aimed to explore the effect of elevated serum [K+] in a rat model of middle cerebral artery occlusion and reperfusion (MCAO/R). Methods: Rats subjected to 90-min MCAO received 2.5% KCL, 1.25% KCL, or a normal saline soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In the present study, our results showed that increasing blood potassium concentrations with IV KCl solution before ischemia can markedly attenuate brain I/R injury as confirmed by decreases in infarct volumes and improvements in NDSs and neuronal morphology. Similar to our results, brain protective effects have also been observed when KCl solution was administered after ischemia in rats (Li et al, ). In addition, experiments with a cardiac arrest and cardiopulmonary resuscitation (CA/CPR) model revealed that high blood potassium levels may impact the tolerance of brain tissue to I/R injury.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, our results showed that increasing blood potassium concentrations with IV KCl solution before ischemia can markedly attenuate brain I/R injury as confirmed by decreases in infarct volumes and improvements in NDSs and neuronal morphology. Similar to our results, brain protective effects have also been observed when KCl solution was administered after ischemia in rats (Li et al, ). In addition, experiments with a cardiac arrest and cardiopulmonary resuscitation (CA/CPR) model revealed that high blood potassium levels may impact the tolerance of brain tissue to I/R injury.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, high‐potassium preconditioning increased SOD activity and reduced MDA levels compared to NS treatment, suggesting that high‐potassium preconditioning exerts antioxidant effects. In contrast, in a previous study by Li et al, elevated blood K + at the moment of reperfusion reduced ROS production but failed to improve antioxidant defenses (Li et al, ). This discrepancy may be due to differences between the two experimental protocols.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations